Control del Gorgojo Cosmopolites sordidus G. Y Metamasius hemipterus L. en Plátano con hongos Entomopatógenos Beauveria bassiana y Metarhizium spp. en San Martín - Ríos Chuquizuta, Roberto Carlos (2007)
With the purpose of dto determiner the effect of the entomopatógenos Beauveria bassiana and Metarhizíum spp in the control of the population of the black weevil (Cosmopolitas sordidus Germar) and rrayado weevil (Metamasius hemipterus), the present test was made in a banana plantation variety "lnguiri" of 3 years of age located to 1 O km of the city of TARAPOTO by the nor1h of the highway Fernando Belaunde Terry (first stage) and in the Laboratory of phytopathologie of the Tropical lnstitute of Culture (second stage) during the month of November of the 2004. The treatments used as much at level of field and laboratory were Witness (To). Beauveria bassíane (T1). Metarhizium spp. (Tz), B, bassiana + Metarhizium spp. (T3) and Beauveria bassiana commercial (T.); being used 04 traps type sandwich of slice of pseudostem of 10 15 cm in length for the capture of weevils at level of field by block or repetition and treatment. The amount of used entomopatógeno (T1, T2 and T 3) g/plant was of 20, whereas brocaril (Bassiana Beauveria commercial: T 4) 1 was only used g/trap; these sprinkled with approximately 5 mililiter of agricultural oil to 15%. The used experimental design at field level was the Blocks Completely at random (DBCA) with 05 treatments and 03 repetitions or blocks; varying its exposition at level from laboratory to design Completely at random (DCA); being used for the comparison of averages the Test of Duncan (a= 0,05). The obtained results show for the field evaluations statistical superiority to us in the captured number of total weevils, collected of the treatments to base Bassiana Beauvsria commercial (Tc) and B. bassiana +Metarhizium (Ta), repelling in a greater rate of capture as much of total weevils and lined weevils. Also, the evaluations at laboratory level allow us to observe better effect in the number of dead and covered with spares weevils of the treatment with B. bassiana + Metarhizium spp (Ta) with 71,7 and 68,0 weevils in average respectively, being different itself significantly from the effect of the other treatments in study; whereas the smaller effects statistically present/display the treatment witness (T 0) and Baauveria bassiana commercial (T.), resulting in a greater average lethat time of total weevils with 47,7 and 39,0 days in average. In relation to the percentage of dead total weevils and esporulados, percentage of mortality of black and lined weevils; it is observed better effects were of the treatments with Beauveria bassiana (T1), Metarhizium spp. (T2) and B. bassiana +Metarhizium spp. (Ta); being different significantly from the treatment witness (To) and Beauveria bassiana commercial (T4).